Kleine Schriften zu zwischenmännlicher Sexualität und Erotik in der muslimischen Gesellschaft - De Martino, Gianni; Schmitt, Arno (Berlin : Arno Schmitt, 1985)
Fonds Suzan Daniel (FSD)
Duits
Monografie